Evaluating collaborative consumption platforms from a consumer perspective - Oliveira, Tiago (2022)
Oliveira, T., Tomar, S., & Tam, C. (2020). Evaluating collaborative consumption platforms from a consumer perspective. Journal of Cleaner Production, 273, [123018]. https://doi.org/10.1016/j.jclepro.2020.123018